Evaluation of new molecule of insecticides against pod fly (Melanagromyza obtusa) of pigeon pea (SAARC Journal of Agriculture, 2014)
Pod fly [Melanagromyza obtusa (Malloch)] is a key biotic constraint for productivity in subsistence crop protection pattern; its damage varies up to 80%; has been estimated about US $ 256 million annually. The research trial was accomplished at Research Farm of SASRD, Nagaland University during Kharif 2011 and 2012 in order to evaluate the new molecules against pod fly. The experiment was consisted 6 treatments (Trizophos 500 g ai. ha-1, Emamectine benzoate 11 g ai. ha-1, Emamectine benzoate 11 g ai. ha-1 + Acetamiprid 30 g ai. ha-1, Flubendiamide 47 g ai. ha-1, Chlorantraniliprole 40 g ai. ha-1 and Spinosade 75 g ai. ha-1) compare with control. The lowest pod damage (9.7% and 9.3%), lowest grain damage (5.3% and 5%) and highest grain yield (1202 kg ha-1 and 1209 kg ha-1) were obtained from Chlorantraniliprole followed by Emamectine benzoate+ Acetamiprid, Spinosade, Emamectine benzoate, Flubendiamide, Trizophos and all the treatments were significantly superior over control. The highest B: C ratio reward (1:4.24) was obtained from Chlorantraniliprole. The results indicated that Chlorantraniliprole was more effectual against pod damage, grain damage, yield and B: C ratio. The safer chemical control methods reduce the pod damage, grain damage and higher yield with high benefit: cost ratio, so therefore chemical control popularizes as an effective, practical alternative and makes lucrative cultivation of pigeon pea. DOI: http://dx.doi.org/10.3329/sja.v12i1.21115 SAARC J. Agri., 12(1): 89-95 (2014)